Designer cell therapy for tissue regeneration - Noyuri Zama; Satoshi Toda (BMC, 2024)
Abstract Cancer cell therapy, particularly chimeric antigen receptor (CAR) T-cell therapy for blood cancers, has emerged as a powerful new modality for cancer treatment. Therapeutic cells differ significantly from conventional drugs, such as small molecules and biologics, as they possess cellular information processing abilities to recognize and respond to abnormalities in the body. This capability enables the targeted delivery of therapeutic factors to specific locations and times. Various types of designer cells have been developed and tested to overcome the shortcomings of CAR T cells and expand their functions in the treatment of solid tumors. In particular, synthetic receptor technologies are a key to designing therapeutic cells that specifically improve tumor microenvironment. Such technologies demonstrate great potential for medical applications to regenerate damaged tissues as well that are difficult to cure with conventional drugs. In this review, we introduce recent developments in next-generation therapeutic cells for cancer treatment and discuss the application of designer therapeutic cells for tissue regeneration.